Integrated Operational Management for Smart & Green Village: A Novel Model Based on Operational Efficiency, Technology, and Community Participation - Mia Kusmiati; Andri Muhamad Nuroni; Hari Mulia; Hadi Sunyata (Harmony Management: International Journal of Management Science and Business, 2024)
Purpose– The objective of this research is to develop an integrated operational management model for Smart & Green Villages (SGVs), combining the principles of smart villages and green villages to promote sustainable, inclusive, and adaptive rural development. This research emphasizes operational efficiency, environmental sustainability, digital technology utilization, and community participation as key pillars. Design/Methodology/Approach – A mixed-methods approach was adopted, involving surveys of villages in Indonesia that have begun adopting SGV principles, in-depth interviews with village officials and key stakeholders, and case studies of villages that have successfully implemented smart technologies and environmentally friendly practices. Data triangulation was applied to strengthen the validity of the findings. Findings – The study shows that integrating functional organizational structures, optimizing digital technologies such as the Internet of Things (IoT) and village information systems, and building participatory community mechanisms significantly improve public service delivery, reduce operational costs, enhance environmental management, and strengthen socio-economic well-being. The study also identified new operational variables, including cost-effective innovation, digital local governance, inter-village shared resources, and socio-environmental audits as a multidimensional evaluation tool. Practical implications – These findings provide a practical framework for policymakers, local governments, and community leaders to implement and evaluate SGV. The multidimensional indicators proposed in this study enable continuous monitoring and adaptation of village operations to local conditions and resource constraints. Originality/Value – This study is one of the first to propose a concrete and replicable SGV operational management model by introducing new variables and multidimensional evaluation indicators. It enriches the theoretical discourse on smart and green village integration while offering actionable strategies for sustainable rural governance.